Analysis of Influencer Credibility Mediating the Impact of Content Marketing on Emina’s Purchase Desision - Salma Salsabila Lestari; Syti Sarah Maesaroh; Adam Hermawan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to analyze the credibility of influencers mediating the impact of content marketing on purchasing decisions for Emina products. The research method used is associative quantitative, with data collected through questionnaires distributed to 170 respondents who are users of Emina Glossy Stain and have seen review content labeled "Tasya Farasya Approve." The results show that influencer credibility, consisting of trustworthiness, attractiveness, and expertise, significantly mediates the impact of content marketing on purchasing decisions. The use of the "Tasya Farasya Approve" label has been proven to influence consumer perceptions and purchasing decisions for Emina products. This indicates the importance of influencer credibility in content marketing strategies to enhance purchasing decisions.